2019
DOI: 10.1007/s00167-019-05435-0
|View full text |Cite
|
Sign up to set email alerts
|

Tibial slope and medial meniscectomy significantly influence short-term knee laxity following ACL reconstruction

Abstract: PurposeTo determine demographic, anatomic, and surgical factors associated with static and dynamic Anterior Tibial Translation (ATT) following ACL reconstruction. The hypothesis was that both static and dynamic ATT would be greater in knees with high tibial slope or that required meniscectomy. MethodsThe authors prospectively enrolled 280 consecutive patients that had primary ACL reconstruction using hamstring autografts at one center for which preoperative tear type, meniscal tears, and medial tibial slope we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…7,9,30 There is growing evidence that steep posterior tibial slope (PTS) has a negative effect on knee stability after ACLR. 5,9,10,33 Steep PTS produces an anteriorly directed shear force when a compressive load is applied to the knee joint, resulting in excessive anterior tibial subluxation (ATS) in extension. 15 Grassi et al 13 investigated the tibiofemoral anatomic parameters in patients with ACLR failure and found that steep PTS (>13°) and excessive ATS in extension (>10 mm) were common findings (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,9,30 There is growing evidence that steep posterior tibial slope (PTS) has a negative effect on knee stability after ACLR. 5,9,10,33 Steep PTS produces an anteriorly directed shear force when a compressive load is applied to the knee joint, resulting in excessive anterior tibial subluxation (ATS) in extension. 15 Grassi et al 13 investigated the tibiofemoral anatomic parameters in patients with ACLR failure and found that steep PTS (>13°) and excessive ATS in extension (>10 mm) were common findings (Figure 1).…”
mentioning
confidence: 99%
“…22 Furthermore, several studies have evaluated the association between steep PTS and the increased risk of concomitant MPHTs in ACL-deficient knees, highlighting the potential risk of ACLR failure if the concomitant MPHTs are not well addressed. 8,9,23…”
mentioning
confidence: 99%
“…2,10 These observations raised concerns regarding clinical outcomes after ACLR, as the altered tibial position can negatively affect the restoration of normal knee kinematics and the improvement of postoperative knee stability. 6,8,11,16,17…”
mentioning
confidence: 99%
“…2,10 These observations raised concerns regarding clinical outcomes after ACLR, as the altered tibial position can negatively affect the restoration of normal knee kinematics and the improvement of postoperative knee stability. 6,8,11,16,17 The risk factors of ATS in extension after ACL injury have been the focus of several recent reports. 24,27 Increases in ATS in extension have been observed in the setting of combined posterior horn of medial and lateral meniscal tears.…”
mentioning
confidence: 99%
“…Thus, the effect of weight/size of calves would be small in this study. Fifth, it might be better to exclude meniscal tears because the anterior tibial displacement was larger after medial meniscectomy in the ACL-deficient/ACL-reconstructed knees 32 , 37 , 40 . All the meniscal tears underwent meniscal repair except one with partial lateral meniscectomy for an incomplete radial tear.…”
Section: Discussionmentioning
confidence: 99%